Analisis Pengaruh Hasil Pemetaan Budaya Mahasiswa BINUS terhadap Jiwa Kewirausahaan: Studi Kasus Tahun Ajaran 2006-2007 - Sari, Synthia Atas; Prabowo, Hartiwi (Journal the Winners: Economics, Business, Management, and Information System Journal, 2008)
Those culture factor than reliabled by people in did interaction with circles, language, think, etc. Article will map out Ubinus reguler student culture using 6 pole culture dimencion by Schwartz and will see the influence than entrepreneurship spirit that should be possessed by leaders in the future. Article used descriptive research method and the data were collected by using questioner. The analysis method was quantitative and qualitative method.Â  The result indicates that conspicuous culture was the embeddedness between individual and group, egaliter (trust, responsibility, loyal with friends or group), and harmonious culture. There are positive influences between the three of dimension culture than entrepreneurship spirit and more influence was embedded ness culture.